The United States and the Iranian nuclear programme : a critical history - Hurst, Steven (Edinburgh University Press, 2018)
Steven Hurst traces the development of the US - Iranian nuclear weapon crisis from the conception of Iran's nuclear programme in 1957 to the signing of the Joint Comprehensive Plan of Action in 2015. Hurst adopts a broader perspective on the Iranian nuclear programme and explains the continued failure of the USA to halt it.